Validating Visual Stimuli of Nature Images and Identifying the Representative Characteristics - Menser, Terri; Baek, Juha; Siahaan, Jacob; Kolman, Jacob M.; Delgado, Domenica; Kash, Bita (Frontiers in Psychology, 2021)
This study fills a void in the literature by both validating images of nature for use in future research experiments and examining which characteristics of these visual stimuli are found to be most representative of nature. We utilized a convenience sample of university students to assess 129 different nature images on which best represented nature. Participants (n=40) viewed one image per question (n=129) and were asked to rate images using a 5-point Likert scale, with the anchors ‘best represents nature’ (5) and ‘least represents nature’ (1). Average ratings across participants were calculated for each image. Canopies, mountains, bodies of water, and unnatural elements were identified as semantic categories of interest, as well as atmospheric perspectives and close-range views. We conducted the ordinary least squares (OLS) regression and the ordered logistic regression analyses to identify semantic categories highly representative of nature, controlling for the presence/absence of other semantic categories. The results showed that canopies, bodies of water, and mountains were found to be highly representative of nature, whereas unnatural elements and close-range views were inversely related. Understanding semantic categories most representative of nature is useful in developing nature-centered interventions in behavioral performance research and other neuroimaging modalities. All images are housed in an online repository and we welcome the use of the final 10 highly representative nature images by other researchers, which will hopefully prompt and expedite future examinations of nature across multiple research formats.